Aspek-Aspek Pendidikan Fiqih di Pesantren untuk Membangun Kesetaraan dan Perdamaian Dunia - Rohiqi Mahtum (LP2M Universitas Ibrahimy, 2023)
Islam is the Universal Religion and a blessing for the whole of Nature, so that the principles taught are also universal without any discrimination against certain groups. As a religion that has shari'a or specific guidelines which we term fiqh, the shari'a must also be universal without distinguishing rules for certain groups unless there are underlying factors. In the above article, we have discussed many editorials that support equality in the field of gender, social affairs, and education as well as reveal some references that Islam is indeed a religion that loves peace. In the social field, it discussed disabilities, the rich, poor and free, and slaves, while in the education sector, it discussed disabled people and convicts. The aspects of fiqh that are discussed are about Worship, Muamalah and Munakahah. All aspects discussed support the existence of the principle of peace which is supported by the basis of equality. As a result, equality and peace have begun to be realized and sought after and supported by the government through many Islamic boarding schools in Indonesia.